Methane and Nitrous Oxide Emissions from Flooded Rice Systems following the End‐of‐Season Drain. Issue 4 (1st July 2015) - Adviento‐Borbe, Maria Arlene; Necita Padilla, Gay; Pittelkow, Cameron M.; Simmonds, Maegen; van Kessel, Chris; Linquist, Bruce
Abstract : Large CH4 and N2 O fluxes can occur from flooded rice ( Oryza sativa L.) systems following end‐of‐season drainage, which contribute significantly to the total growing‐season greenhouse gas (GHG) emissions. Field and laboratory studies were conducted to determine under what soil water conditions these emissions occur. In three field studies, GHG fluxes and dissolved CH4 in the soil pore water were measured before and after drainage. Across all fields, approximately 10% of the total seasonal CH4 emissions and 27% of the total seasonal N2 O emissions occurred following the final drain, confirming the importance of quantifying postdrainage CH4 and N2 O emissions. Preplant fertilizer N had no effect on CH4 emissions or dissolved CH4 ; however, increased postdrainage N2 O fluxes were observed at higher N rates. To determine when postdrainage sampling needs to take place, our laboratory incubation study measured CH4 and N2 O fluxes from intact soil cores from these fields as the soil dried. Across fields, maximum CH4 emissions occurred at approximately 88% water‐filled pore space (WFPS), but emissions were observed between 47 and 156% WFPS. In contrast, maximum N2 O emissions occurred between 45 and 71% WFPS and were observed between 16 and 109% WFPS. For all fields, gas samplings between 76 and 100% WFPS for CH4 emissions and between 43 and 78% WFPS for N2 O emissions was necessary to capture 95% of these postdrainage emissions. We recommend that frequent gas sampling following drainage be included in the GHG protocol of total GHG emissions.